3D Organoids: An Untapped Platform for Studying Host–Microbiome Interactions in Esophageal Cancers - Samuel Flashner (MDPI AG, 2021)
The microbiome is an emerging key co-factor in the development of esophageal cancer, the sixth leading cause of cancer death worldwide. However, there is a paucity of data delineating how the microbiome contributes to the pathobiology of the two histological subtypes of esophageal cancer: esophageal squamous cell carcinoma and esophageal adenocarcinoma. This critical knowledge gap is partially due to inadequate modeling of host–microbiome interactions in the etiology of esophageal cancers. Recent advances have enabled progress in this field. Three dimensional (3D) organoids faithfully recapitulate the structure and function of the normal, preneoplastic, and neoplastic epithelia of the esophagus ex vivo and serve as a platform translatable for applications in precision medicine. Elsewhere in the gastrointestinal (GI) tract, the co-culture of 3D organoids with the bacterial microbiome has fostered insight into the pathogenic role of the microbiome in other GI cancers. Herein, we will summarize our current understanding of the relationship between the microbiome and esophageal cancer, discuss 3D organoid models of esophageal homeostasis, review analogous models of host–microbiome interactions in other GI cancers, and advocate for the application of these models to esophageal cancers. Together, we present a promising, novel approach with the potential to ameliorate the burden of esophageal cancer-related morbidity and mortality via improved prevention and therapeutic interventions.